2019
DOI: 10.1111/1758-2229.12808
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic–genotypic analysis of GGDEF/EAL/HD‐GYP domain‐encoding genes in Pseudomonas putida

Abstract: Cyclic diguanylate (c-di-GMP) is a broadly conserved bacterial signalling molecule that modulates diverse cellular processes, such as biofilm formation, colony morphology and swimming motility. The intracellular level of c-di-GMP is controlled by diguanylate cyclases (DGCs) with GGDEF domain and phosphodiesterases (PDEs) with either EAL or HD-GYP domain. Pseudomonas putida KT2440 has a large group of genes on its genome encoding proteins with GGDEF/EAL/HD-GYP domains. However, phenotypic-genotypic correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…We then transformed the plasmids into the wild-type strain, bifA mutant (Δ bifA ), fleQ mutant (Δ fleQ ), and fleQ - bifA double mutant (Δ fleQ Δ bifA ) and further tested their GFP fluorescence intensity. Our previous study has shown that deletion of BifA (a phosphodiesterase with c-di-GMP degradation activity) causes increased c-di-GMP levels in P. putida ( 23 ). The results showed that GFP fluorescence intensity of the Δ bifA mutant containing the lapE - gfp fusion reporter was much higher than that of the wild type, whereas the fluorescence intensity of the Δ bifA mutant containing the cyaA - gfp fusion reporter was lower than that of the wild type ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then transformed the plasmids into the wild-type strain, bifA mutant (Δ bifA ), fleQ mutant (Δ fleQ ), and fleQ - bifA double mutant (Δ fleQ Δ bifA ) and further tested their GFP fluorescence intensity. Our previous study has shown that deletion of BifA (a phosphodiesterase with c-di-GMP degradation activity) causes increased c-di-GMP levels in P. putida ( 23 ). The results showed that GFP fluorescence intensity of the Δ bifA mutant containing the lapE - gfp fusion reporter was much higher than that of the wild type, whereas the fluorescence intensity of the Δ bifA mutant containing the cyaA - gfp fusion reporter was lower than that of the wild type ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another emerging theme is that the integration of positive or negative feedback loops is probably common for c-di-GMP signalling systems, presumably for rapid signal amplification and noise attenuation. The mechanisms discussed in this minireview are likely to be operational in many pseudomonads, considering that the orthologs of flgZ, mapZ and fimW and many genes implicated in c-di-GMP signalling, flagellum/pili-dependent motility, and surface adhesion are found in all the sequenced pseudomonads (Choy et al, 2004;Feil et al, 2005;Duque et al, 2013;Nogales et al, 2015;Wang et al, 2019;Nie et al, 2020). It is nonetheless important to note that adaptive evolution has generated phenotypic and genotypic diversity among the pseudomonads (Silby et al, 2011;Redondo-Nietoet al, 2012;Chandler et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies of Escherichia coli and other model organisms suggested that cellular c-di-GMP concentrations influence flagellum-dependent motility, as evidenced by the motility defects caused by the deletion of dgc and pde genes (Simm et al, 2004;Christen et al, 2007). Studies on P. aeruginosa and Pseudomonas putida confirmed the role of c-di-GMP in the regulation of flagellumdependent motility and established functional links between several c-di-GMP signalling proteins and flagellar biosynthesis or function (Caiazza et al, 2007;Kuchma et al, 2007;Merritt et al, 2007;Aragon et al, 2015;Nie et al, 2020). Today, it is firmly established that c-di-GMP-mediated flagellar gene expression is a major mechanism used by pseudomonads to downregulate flagellar activity for long-term adaptation (Wolfe and Visick, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the identification of proteins that function as receptors/effectors for the c-di-GMP system has proven to be more complex. It is known that c-di-GMP can bind to various classes of proteins that differ in structure and amino acid sequences [ 16 , 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%